The efficacy of etodolac and ibuprofen, regarding gender, on pain, edema and trismus after impacted lower third molar surgery: A randomized prospective clinical split-mouth study - Silva, Leonardo de Freitas [UNESP]; Reis, Erik Neiva Ribeiro de Carvalho [UNESP]; Faverani, Leonardo Perez [UNESP]; Bassi, Ana Paula Farnezi [UNESP] (Medicina Oral, S.L., 2021)
Background: This study aimed to conduct a randomized prospective study about the efficacy of etodolac and ibuprofen on trismus, pain and edema regarding gender of patients submitted to impacted lower third molar teeth extraction. Material and Methods: Thirty patients aging between 16 and 35 year-old were submitted to the exodontia of impacted lower third molars. During the postoperative period, patients received nine ibuprofen (600 mg) or etodolac (300 mg) pills via oral administration immediately after surgery and repeated doses every eight hours during three days. Patients were evaluated regarding pain, trismus and edema. Results: Sixteen men and fourteen women participated of the study. No statistical difference was established regarding gender according to the evaluated parameters. However, etodolac use showed better results regarding pain, trismus and edema. Conclusions: Pain, edema and trismus after impacted third molars extraction were not influenced by gender.
Keywords: Molar; Third; sex; Tooth extraction